Historiographical shifts in iconoclasm: Colonial to contemporary narratives of temple desecration under the Mughals (Critical Journal of Social Sciences, 2026)
This study explores the changing historiographical trends surrounding iconoclasm, particularly temple desecration during the Mughal period. It suggests that explanations of temple desecration should move beyond interpretations limited to religious policy or political strategies, and instead, consider temples as multi-functional institutions whose social, educational, economic, and religious centrality contributed to their vulnerability. The study underscores that the history of iconoclasm encompasses not only the acts themselves, but also how they have been understood and narrated by successive generations of historians contesting the memory of temple desecration. This idea stems from long-standing debates in South Asian historiography about desecration and adaptation of sacred sites, embodying intersections of power, authority, and domination arguments. Emerging with the Islamic invasions in the subcontinent, these practices were initially tied to strategies for resource acquisition before gradually transforming into tools of political control and social regulation. Over time, varied interpretations of these practices have emerged. Colonialist and nationalist interpretations stressed religious intolerance, while recent scholarship situated these within broader political, social, economic, and cultural contexts. The integration of both quantitative and qualitative methods in contemporary scholarship further contributed to diverse reinterpretations, representing an important milestone in historical discourse of iconoclasm.